Investigation into the effect of fatty acids on the yield and replication of rotavirus in cell culture - Sander, Willem Jacobus (University of the Free State, 2019)
Rotavirus (RV) remains one of the leading causes of severe dehydrating diarrhoea in infants and young children. The successful replication of RV relies on the formation of viroplasms, which consist of several viral proteins and host lipid droplets (LDs). Several studies have indicated that the absence of LDs or fatty acids (FAs) for the formation of LDs prevent the formation of viroplasms and subsequently severely hamper RV replication. Lipid droplets are well-known for their storage of fatty acids and their downstream metabolites that can play roles in immunological response toward invading pathogens. Furthermore, the type of FAs within LDs plays critical roles in shaping both the type and strength of immune responses. This study sought to determine the effects that supplementation of MA104 cells with FAs of varying saturation could have on RV replication. The effects of supplementing MA104 cells with albumin (as control), stearic acid (SA, 18:0), oleic acid (OA, 18:1) and γ-linolenic acid (GLA, 18:2) on the lipid profile of M104 cells were determined using gas chromatography. Results indicated that each supplementation was able to change the lipid profile of MA104 cells in unique ways. Albumin supplementation showed no significant difference from the unsupplemented and uninfected control, while SA supplementation appeared to lower/increase some FAs, but not itself, when compared to unsupplemented and uninfected control. Oleic acid supplementation increased the relative percentage of itself, while GLA supplementation increased both the relative percentage of itself and arachidonic acid (AA) compared to the unsupplemented and uninfected control. The subsequent infection of supplemented MA104 cells further modulated the lipid profile of MA104 cells. Infection, of cells supplemented with GLA, showed an increase in the relative percentage of both GLA and AA when compared to the supplemented uninfected control. Interestingly, the study found that RV decreased the amount of GLA and AA in cells supplemented with GLA, possibly indicating that the metabolism of these FAs is driven to produce prostaglandin E2 (PGE2), a well-known modulator for immunity. The use of tissue culture infection doses 50 (TCID50) showed that the supplementation of M104 cells with unsaturated FAs (OA and GLA) increased the rate of RV replication when compared to the unsupplemented and infected control. In particular, the supplementation of GLA showed to be an effective enhancer of RV replication. In contrast, supplementation with albumin and saturated FAs (SA) showed no significance in rate of replication when compared to the unsupplemented and uninfected controls. Detection of PGE2 using ELISA showed that RV can increase the production of PGE2 regardless of supplementation. However, the supplementation of MA104 cells with GLA led to a 2-fold increase in the amount of PGE2 compared to unsupplemented and infected MA104 cells. By using confocal laser scanning microscopy, it was shown that LDs, PGE2 and NSP2 (viral protein present in viroplasms) co-localized in supplemented and uninfected MA104 cells. Co-localization between NSP2 and PGE2 was also observed for the first time during the study indicating a possible role for viroplasms during the increased production of PGE2. Together, results from this study shows that unsaturated FAs (OA and GLA) can increase the replication of RV. Although the exact mechanism behind this effect remains unknown, data indicates that there could be a role for PGE2. Thus, by elucidating the mechanism by which unsaturated FAs (and possibly PGE2) increase the replication rate of RV, novel anti-viral strategies against RV could be developed.
Dissertation (M.Sc. (Microbiology))--University of the Free State, 2019
Keywords: Tissue culture; Rotavirus; Rotavirus SA11 strain; Fatty acids; Stearic acid; Oleic acid; Y-linolenic acid; Prostaglandin E2; Viral infection; Viral immunity; Viral replication